Pelatihan Pembuatan Media Pembelajaran Berbasis Mobile Bagi Guru SMP - Susila, Aceng Ahmad Rodian; Nasrullah, Iman; Denni, Irdam; Bhakti, Demmy Dharma (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of information technology has now affected various aspects of life, including the world of education. An educator is required to be able to follow and apply technology along with the times in the teaching and learning process. The application of this technology can be used in mobile-based learning media, as a solution so that the material delivered by educators looks more attractive. Thus, community service activities were carried out in the form of training in making mobile-based learning media for junior high school teachers. This activity aims to improve the ability of educators to create mobile-based learning media. The training activities were attended by 40 science teachers from the Cisompet sub-district. The training is carried out in stages, namely 1) preparation; 2) material exposure; 3) making learning media by participants; 4) task collection; and 5) evaluation. The results of the participants' responses to this training activity were positive. From the questionnaire distributed to the participants, 90.3% stated that the training material was very good and useful for the participants.